Synthesis and characterisation of nanostructured TiO2/SBA-15 and Ag-TiO2/SBA-15 mesoporous composites - Nguyen Van Nghia; Ho Xuan Vinh; Nguyen Tien Trung; Nguyen Phi Hùng (My University, 2015)
Synthesis and characterisation of nanostructured TiO2/SBA-15 and Ag-TiO2/SBA-15 mesoporous composites
Keywords: TiO2/SBA-15